2011
DOI: 10.1016/j.neuroimage.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Auditory cortex activation is modulated by emotion: A functional near-infrared spectroscopy (fNIRS) study

Abstract: Visual emotional stimuli evoke enhanced activation in early visual cortex areas which may help organisms to quickly detect biologically salient cues and initiate appropriate approach or avoidance behavior. Functional neuroimaging evidence for the modulation of other sensory modalities by emotion is scarce. Therefore, the aim of the present study was to test whether sensory facilitation by emotional cues can also be found in the auditory domain. We recorded auditory brain activation with functional near-infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 110 publications
12
110
1
Order By: Relevance
“…However, it is possible to understand NVC by using a correlation function between the neuronal and hemodynamic responses. 14 NIRS studies with auditory cortex activation have been also reported for both adults [27][28][29] and infants. 30,31 These studies are mainly based on linguistic viewpoint.…”
Section: Discussionmentioning
confidence: 95%
“…However, it is possible to understand NVC by using a correlation function between the neuronal and hemodynamic responses. 14 NIRS studies with auditory cortex activation have been also reported for both adults [27][28][29] and infants. 30,31 These studies are mainly based on linguistic viewpoint.…”
Section: Discussionmentioning
confidence: 95%
“…Considering that the previously mentioned probing technique would be inappropriate for the current research (given the tasks high event rate), it is necessary to use an alternative, non-intrusive method of gathering physiological stress data to compliment findings regarding the subjective state of individuals. The functional Near-Infrared Spectroscopy (fNIRS), which is primarily employed to assess cerebral activation differences in local and global discrimination conditions has also been used in a range of research as a measurement of physiological stress (Tanida, Katsuyama & Sakatani, 2008;Plichta et al, 2011;Kirilina et al, 2012). Indeed, Ishii et al, (2008) investigated the use of fNIRS as an alternative technique for mental state analysis, and found results that indicate its' suitability as a tool for mental state evaluation.…”
Section: Functional Near-infrared Spectroscopymentioning
confidence: 99%
“…Also fNIRS provides silent recordings that are free from magnetic and electrical artefacts, and thus is highly suited to auditory research and is safe for repeated use in CI recipients (Sevy et al, 2010). Further, it is possible to measure functional responses to auditory stimulation in auditory cortex using fNIRS (Ohnishi et al, 1997;Minagawa-Kawai et al, 2002;Remijn and Kojima, 2010;Sevy et al, 2010;Plichta et al, 2011).…”
Section: Introductionmentioning
confidence: 99%